2022
DOI: 10.5937/ekopolj2204151s
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 pandemic and the economic results of agriculture in the European Union

Abstract: The Covid-19 pandemic has brought numerous economic challenges to countries around the world. The specificities of certain economy sectors determined the character and intensity of the impact of this health crisis on their results. The purpose of the paper is to analyse the impact that the Covid-19 pandemic has had on the economic results of agriculture in the European Union countries. Comparative analysis and cluster analysis are used in the research. The general conclusion of the paper is that the Covid-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Harvest delays and increased food losses, especially for perishables, due to mobility restrictions in the European Union were also reported by Stanisic et al [40]. The study concluded that "the COVID-19 pandemic did not change the importance of agriculture for the economic performance of individual countries" and "did not have a negative impact on the contribution of agriculture to GDP" [40]. Evidence from Malaysia through observations by Say Peng et al [41] suggested that labour shortages due to mobility restrictions led to a decline in agri-food production.…”
Section: Agriculture and Rural Areassupporting
confidence: 60%
See 1 more Smart Citation
“…Harvest delays and increased food losses, especially for perishables, due to mobility restrictions in the European Union were also reported by Stanisic et al [40]. The study concluded that "the COVID-19 pandemic did not change the importance of agriculture for the economic performance of individual countries" and "did not have a negative impact on the contribution of agriculture to GDP" [40]. Evidence from Malaysia through observations by Say Peng et al [41] suggested that labour shortages due to mobility restrictions led to a decline in agri-food production.…”
Section: Agriculture and Rural Areassupporting
confidence: 60%
“…In Arkansas, the agriculture and forestry sector as a whole suffered less during the first year of the pandemic with minor losses, but at the county and local level, the impact was more pronounced due to the distribution of industries, as reported by English et al [39]. Harvest delays and increased food losses, especially for perishables, due to mobility restrictions in the European Union were also reported by Stanisic et al [40]. The study concluded that "the COVID-19 pandemic did not change the importance of agriculture for the economic performance of individual countries" and "did not have a negative impact on the contribution of agriculture to GDP" [40].…”
Section: Agriculture and Rural Areasmentioning
confidence: 66%
“…The Government ordered an extraordinary recess of judgments from 15 March 2020. 19 During the period of the extraordinary jurisdictional recess the courts did not hold any hearings. With the end of the extraordinary recess, it was not possible to hold a trial requiring personal presence during the state of danger, 20 but there was a wider possibility to use written pleadings and electronic hearings.…”
Section: Impact Of Covid 19 On Agricultural Case Lawmentioning
confidence: 99%
“…In order to maintain food security, the Commission partly provided guidelines for the safe operation of the food supply chain, and partly decided to introduce measures to directly support farmers and rural areas, which included direct subsidies, extraordinary market subsidies and measures to simplify the CAP [19].…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects of the pandemic on the economy, trade, human health, society, environment, tourism, culture, education and more are now well-documented [9][10][11][12][13][14][15]. According to the World Health Organization [16], globally there have been 775 million confirmed cases, including 7.03 million deaths in more than 210 countries, and the International Monetary Fund [17] estimates that the global economy shrunk by 4.4% in 2020, which is the biggest decline since the Great Depression of the 1930s.…”
Section: Introductionmentioning
confidence: 99%